2000
DOI: 10.2307/2676320
|View full text |Cite
|
Sign up to set email alerts
|

Life Stress, Anger and Anxiety, and Delinquency: An Empirical Test of General Strain Theory

Abstract: General strain theory (Agnew 1992) departs from traditional strain theories by emphasizing the role of the individual's affective responses to negative life experiences in fostering deviant behavior In this analysis, we examine the central hypotheses of general strain theory using data from a three-wave panel study of high school youths in the Boston metropolitan area (N = 939). Covariance structure models reveal that anger and hostility in response to negative life events do play a causal role in fostering mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
345
3
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 400 publications
(388 citation statements)
references
References 57 publications
31
345
3
7
Order By: Relevance
“…Many of the main concepts pertaining to GST have been thoroughly tested, most specifically, the direct relationship between strain and delinquency. Overall, the research has consistently found a positive relationship between strain and delinquent behavior (e.g., Agnew, 2002;Agnew et al, 2002;Agnew & White, 1992;Aseltine et al, 2000;Brezina, Piquero, & Mazerolle, 2001;Hay, 2003;Paternoster & Mazerolle, 1994). Indeed, in almost every published test of GST, at least one measure of strain has been found to positively influence delinquency.…”
Section: Empirical Research On Gstmentioning
confidence: 96%
See 3 more Smart Citations
“…Many of the main concepts pertaining to GST have been thoroughly tested, most specifically, the direct relationship between strain and delinquency. Overall, the research has consistently found a positive relationship between strain and delinquent behavior (e.g., Agnew, 2002;Agnew et al, 2002;Agnew & White, 1992;Aseltine et al, 2000;Brezina, Piquero, & Mazerolle, 2001;Hay, 2003;Paternoster & Mazerolle, 1994). Indeed, in almost every published test of GST, at least one measure of strain has been found to positively influence delinquency.…”
Section: Empirical Research On Gstmentioning
confidence: 96%
“…Research has failed to find consistent support for the conditioning hypothesis of GST in explaining delinquency (e.g., Agnew & White, 1992;Aseltine et al, 2000;Brezina, 1996;Hay, 2003;Hoffmann & Miller, 1998;Mazerolle & Maahs, 2000;Paternoster & Mazerolle, 1994;Piquero & Sealock, 2000;Robbers, 2004). A number of possible conditioning factors have been examined including social support (e.g., Robbers, 2004), self-esteem (e.g., Hoffmann & Miller, 1998), depression (e.g., Piquero & Sealock, 2000), anger (e.g., Hay, 2003), delinquent peer exposure (e.g., Piquero & Sealock, 2004), religiosity (e.g., Jang & Johnson, 2005), and others.…”
Section: Empirical Research On Gstmentioning
confidence: 99%
See 2 more Smart Citations
“…This theory provides an explanation of why an individual commits a delinquent act when needs and/or goals go unmet (Gentle-Genitty, 2013). The theory suggests that deviant behaviors --which go against societal norms-arise from some discrepancy between personal goal motivation and opportunities for goal achievement (Agnew, 1992;Aseltine, Gordon, & Gore, 2000;Brezina, Piquero, & Mazerolle, 2001). The final theory informing the work is social disorganization theory.…”
Section: Theories Of Youth Violencementioning
confidence: 99%